From laboratory to point of entry: development and implementation of a loop‐mediated isothermal amplification (LAMP)‐based genetic identification system to prevent introduction of quarantine insect species. Issue 6 (12th March 2018) - Blaser, Simon; Diem, Hanspeter; von Felten, Andreas; Gueuning, Morgan; Andreou, Michael; Boonham, Neil; Tomlinson, Jennifer; Müller, Pie; Utzinger, Jürg; Frey, Jürg E; Bühlmann, Andreas
Abstract: BACKGROUND: Rapid genetic on‐site identification methods at points of entry, such as seaports and airports, have the potential to become important tools to prevent the introduction and spread of economically harmful pest species that are unintentionally transported by the global trade of plant commodities. This paper reports the development and evaluation of a loop‐mediated isothermal amplification (LAMP)‐based identification system to prevent introduction of the three most frequently encountered regulated quarantine insect species groups at Swiss borders, Bemisia tabaci, Thrips palmi and several regulated fruit flies of the genera Bactrocera and Zeugodacus . RESULTS: The LAMP primers were designed to target a fragment of the mitochondrial cytochrome c oxidase subunit I gene and were generated based on publicly available DNA sequences. Laboratory evaluations analysing 282 insect specimens suspected to be quarantine organisms revealed an overall test efficiency of 99%. Additional on‐site evaluation at a point of entry using 37 specimens performed by plant health inspectors with minimal laboratory training resulted in an overall test efficiency of 95%. During both evaluation rounds, there were no false‐positives and the observed false‐negatives were attributable to human‐induced manipulation errors. To overcome the possibility of accidental introduction of pests as a result of rare false‐negative results, samples yielding negative results in the LAMP method were also subjected to DNA barcoding. CONCLUSION: Our LAMP assays reliably differentiated between the tested regulated and non‐regulated insect species within <1 h. Hence, LAMP assays represent suitable tools for rapid on‐site identification of harmful pests, which might facilitate an accelerated import control process for plant commodities. © 2018 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Control of plant commodities at points of entry is a first‐line defense against pest invasions. We present an identification system for insect pests enabling rapid genetic on‐site testing within 1 h.